Synthesis and antiproliferative activities of thioxoflavonoids on three human cancer cells. Issue 17 (2nd September 2019) - Li, Wei; Han, Peipei; Cai, Shuanglian; Wang, Qiuan
Abstract: Two series of fifteen novel thioxoflavonoids2a-2h and4a-4g were synthesized from corresponding flavonoids1a-1h and3a-3g by reacting with Lawesson's reagent, respectively. Their in vitro antiproliferative activities were evaluated on a panel of three human cancer cell lines (Hela, HCC1954 and SK-OV-3) using cell counting kit-8 (CCK-8) assay. The results showed that most of the target compounds exhibited moderate to good antiproliferative activities against the three human cancer cell lines. In particular, thioxoflavonoids2f and2g showed the strongest antiproliferative activity on all three human cancer cell lines with IC50 values ranging from 3.34 to 4.67 μM, 4f showed the best antiproliferative activity on Hela cells (IC50 2.30 μM), 2e showed the best antiproliferative activity on HCC1954 cells (IC50 2.13 μM) and SK-OV-3 cells (IC50 2.33 μM). The antiproliferative activities may be involved in their antioxidant activity, which can be speculated by their ability to scavenge free radicals and by their capacity of affecting key redox enzymes. Abstract :